Income distribution and poverty in Argentina postdefault (Polis (Santiago), 2018)
Daniel García Delgado presents the different debates concerning the multiple approaches involved in the construction of a national strategy of development with equity in Argentina. Four dimensions are presented. In first place, the author remarks the positive macroeconomic indicators after 3 years of economic recovery since the 2001-2002 default crisis. Some “yellow lights” are, however, emphasized, most of which concerning the recent evolution of poverty, income distribution and labour market evolution. Secondly, the existence of a treble and resilient gap is highlighted; its dimensions (social, spatial and temporal) are associated to the model of capital concentration and centralization of the last three decades. Thirdly, the author argues that modifying these three gaps implies further political measures, objectives and values in order to constitute a wholly built, sustainable and inclusive development project. High exchange rates, increased primary superavit and taxing commodities exportations, constitute the necessary but not sufficient economic policies. An inclusive development project, necessarily different from the neoliberal recent past, implies some key dimensions such as: i) the definition and specialization on a productive profile; ii) the role assigned to the State; iii) the regional and global framing of this project and; iv) the social coalition that will defend and sustain it. Last, an essential association between policies orientations and political values is defended. On the eve of the 200 anniversary of Argentinean independence, national goals must be established not only concerning economic growth but also, and centrally, the reduction of unemployment, poverty and inequity.
Keywords: development; Argentina; strategy; growth; sustainability; crisis